Effect of Incentives to Employee Performance in Private Sectors in Rwanda a Case Study of Spedag Interfreight Rwanda Ltd - UMUTONI , Olive; Narayan Singh, Satyendra (International Journal of Scientific Research and Management (IJSRM), 2022)
This research examined the effect of incentives to employee performance in private sectors in Rwanda, a case of SPEDAG Interfreight Rwanda Ltd. This research achieved the following objectives: To analyze practices of motivation factors at SPEDAG Interfreight Rwanda Ltd; To explore the employees’ performance at SPEDAG Interfreight Rwanda Ltd and To establish the relationship between incentives factors and employee performance in private sectors. The research also compared two variables which are independent and dependent variables. This study was designed as a case of SPEDAG Interfreight Rwanda Ltd using survey method; a case study was described as “examining the effect of incentives to employee performance in private sectors in Rwanda” assuming that the researcher acquired knowledge regarding the subject under review from in-depth exploration of the study. Qualitative analysis was used to carefully observe the whole situation. All the respondents from the population of SPEDAG Interfreight Rwanda Ltd responded to research questionnaires. The researcher used questionnaires to collect data, as far as this study was concerned, the population comprised employees of SPEDAG Interfreight Rwanda Ltd in different departments targeting 430 employees to describe target population of a study as the point of focus from which a generalization was made regarding the research findings. Thus, a sample size of 81 employees as respondents were considered from total population of 430 people. Researcher used primary and secondary data to get all information needed in this study, the quantitative data was analyzed using descriptive and inferential statistics after running the data collected through the Statistical Package for Social Sciences. Based on the results from chapter four, the study concluded there is significant impact of motivation factors on employee performance at Spedag Interfreight Rwanda Ltd. From the result obtained, the study shows that compensation has an impact on employee